Physical therapy interventions to manage pain in Parkinson’s disease: A systematic review - Thays Tanner Henemann; Lauren Truchem; Juliana Siega; Luis Henrique Paladini; Vera Lúcia Israel (Human Movement, 2023)
Purpose Pain is a common non-motor symptom in Parkinson’s disease (PD), affecting about 40% of this population. Non-drug treatments and physical exercises, including physical therapy, are recommended options to ease PD pain. However, there are gaps in the literature regarding the treatment of this symptom, as well as few clinical trials assessing possible physical therapy interventions to manage PD pain. Hence, the objective of this study was to verify and analyse the physical therapy treatments available in the literature to manage pain in PD patients.